2017
DOI: 10.1038/s41467-017-01864-y
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of naturally occurring ESR1 mutations in breast cancer cell lines modelling endocrine resistance

Abstract: Resistance to endocrine therapy remains a major clinical problem in breast cancer. Genetic studies highlight the potential role of estrogen receptor-α (ESR1) mutations, which show increased prevalence in the metastatic, endocrine-resistant setting. No naturally occurring ESR1 mutations have been reported in in vitro models of BC either before or after the acquisition of endocrine resistance making functional consequences difficult to study. We report the first discovery of naturally occurring ESR1 Y537C and ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
114
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 123 publications
(134 citation statements)
references
References 45 publications
12
114
0
2
Order By: Relevance
“…[20][21][22] Using in vitro-derived ESR1 mutant cell line models generated using CRISPR/Cas9 technology, or through natural selection of cells in hormone-deprived conditions, Martin et al 23 showed that there was a high overlap between ER chromatin binding sites of estrogen-stimulated WT receptor and hormone-deprived mutant receptors. [20][21][22] Using in vitro-derived ESR1 mutant cell line models generated using CRISPR/Cas9 technology, or through natural selection of cells in hormone-deprived conditions, Martin et al 23 showed that there was a high overlap between ER chromatin binding sites of estrogen-stimulated WT receptor and hormone-deprived mutant receptors.…”
Section: Biology Of Esr1 Mutations In Preclinical Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…[20][21][22] Using in vitro-derived ESR1 mutant cell line models generated using CRISPR/Cas9 technology, or through natural selection of cells in hormone-deprived conditions, Martin et al 23 showed that there was a high overlap between ER chromatin binding sites of estrogen-stimulated WT receptor and hormone-deprived mutant receptors. [20][21][22] Using in vitro-derived ESR1 mutant cell line models generated using CRISPR/Cas9 technology, or through natural selection of cells in hormone-deprived conditions, Martin et al 23 showed that there was a high overlap between ER chromatin binding sites of estrogen-stimulated WT receptor and hormone-deprived mutant receptors.…”
Section: Biology Of Esr1 Mutations In Preclinical Studiesmentioning
confidence: 99%
“…For instance, Martin et al 23 were the first to model in vitro the natural acquisition of ESR1 mutations in ER-positive breast cancer cells. For instance, Martin et al 23 were the first to model in vitro the natural acquisition of ESR1 mutations in ER-positive breast cancer cells.…”
Section: Biology Of Esr1 Mutations In Preclinical Studiesmentioning
confidence: 99%
See 3 more Smart Citations